P-496 "The plethora of information can be overwhelming…": A mixed methods study exploring the sources of fertility information. (30th June 2022) - Grace, B; Shawe, J; Stephenson, J
Abstract: Study question: What sources are used when seeking fertility information and how informed do individuals feel about these sources? Summary answer: Sources discussed with varying levels of access, reliability, and trust included: school education; healthcare-professionals; websites (general/government/medical); social-media/online-forums; family/friends; smartphone-apps; books/magazines/newspapers; fertility-products; sexual-health clinics/centres and charities. What is known already: As the average age of first-time parents continues to rise, health policies have highlighted the importance of optimising reproductive health through better knowledge. There has also been a concerted effort by various reproductive health groups to improve fertility awareness. Understanding the different sources of information used by the target audience is important for disseminating and improving fertility knowledge. This mixed-methods study therefore aimed to assess the different sources used by individuals when seeking fertility information and the perceived accessibility and reliability of these sources in order to understand what's working, what isn't, and opportunities for improvement. Study design, size, duration: Mixed method research was conducted via a UK-wide cross-sectional survey and semi-structed interviews. Results were obtained from 1, 082 survey respondents and in-depth interviews with 15 men and 20 women. Interviewees were purposively sampled to include men and women from the reproductive age range (18-45 years) and of varying ethnic and educational backgrounds. Participants/materials, setting, methods: Survey participants were recruited nationwide via online newspaper and social media adverts and of those who agreed to a follow-up interview, 35 were included this study. Interviews lasted an hour on average. Data was transcribed and analysed via thematic framework analysis. Favourable ethical opinion was given by University College London Research Ethics Committee. Main results and the role of chance: When asked about knowledge from school education, 89.3% of survey respondents selected 'good'/'some knowledge' on the biology of reproduction and pregnancy-prevention, contrasting with 76.4% who reported having 'no knowledge'/'do not recall' of factors affecting fertility or protection of fertility. While healthcare-professionals were ranked the most trusted but not easily accessible source, the internet was the most used, due to accessibility and perceived anonymity. However, many internet sources weren't trusted, with a respondent citing "the plethora of information can be overwhelming, you don't know what you can trust." Male, 27, White. Interviews highlighted family and friends as important sources, but with recurring themes around awkwardness and embarrassment discussing the topic. For example, one respondent recalled that her first discussion of sex with her mother was on her wedding night stating, " …Mum, I'm 28! And you're just discussing this with me now?" Female, 36, Asian. Social media was seen as a useful tool for wider reach of different population groups. Mobile apps (e.g. cycle-trackers) were cited but with concerns over information reliability; while others discussed using fertility products like sperm and ovulation kits to better understand their fertility. Other sources discussed include health centres, sexual health clinics, charities and other third-party organisations. Limitations, reasons for caution: A key methodological limitation of this study is that the interviewees were self-selected, which has implications for generalisability. The results necessarily reflect the views of those who were willing to participate. Additionally, the online recruitment method could result in potential bias towards respondents of higher socioeconomic status. Wider implications of the findings: School education remains a consistent but sometimes inadequate source of fertility information. Ensuring better fertility information during school education may offset the impact of unreliable sources. In addition to websites, apps and products based on robust scientific evidence, there remains an important need for additional training for primary healthcare-professionals. Trial registration number: N/A